Myotonic Dystrophy Disease Mechanism, Current Management and Therapeutic Development (Springer Singapore, 2018)
This book provides an essential overview combining both clinical and fundamental research advances in myotonic dystrophy. The pathomechanism of myotonic dystrophy has long been unclear, but in the past decade, our understanding has shifted to a novel disease mechanism concept: "RNA disease". Parallel to these advances in elucidating the pathophysiology, translational research is also progressing rapidly. The current challenge lies in assessing the effectiveness of treatment, and as such, there is a growing interest in observational studies of the disease's various clinical symptoms. The book introduces readers to the molecular mechanisms within each organ and the resultant clinical features, which are presented together. In particular, it focuses on the central nervous system, since the pathology of the brain (central nervous system manifestation) has rarely been addressed systematically and will pose a persistent challenge, even if therapies have greatly advanced in the future. In addition, the book addresses the latest developments, such as research using patient-derived iPS cells and therapeutic research. Myotonic Dystrophy provides essential information for neurologists and researchers with an interest in muscle disease, including muscular dystrophy. Furthermore, since the disease involves various complications of the brain, heart, metabolism, etc., the book will be of great value to clinicians and researchers in the cardiovascular sciences, endocrinology, diabetes, dementia, and neuropsychology, as well as genetic specialists.